Cardiac Biomarkers in Hyperthyroid Cats - Sangster, J.K. (J Vet Intern Med, 2013)
BACKGROUND: Hyperthyroidism has substantial effects on the circulatory system. The cardiac biomarkers NT‐proBNP and troponin I (cTNI) have proven useful in identifying cats with myocardial disease but have not been extensively investigated in hyperthyroidism. HYPOTHESIS: Plasma NT‐proBNP and cTNI concentrations are higher in cats with primary myocardial disease than in cats with hyperthyroidism and higher in cats with hyperthyroidism than in healthy control cats. ANIMALS: Twenty‐three hyperthyroid cats, 17 cats with subclinical hypertrophic cardiomyopathy (HCM), and 19 euthyroid, normotensive healthy cats ≥8 years of age. Fourteen of the hyperthyroid cats were re‐evaluated 3 months after administration of radioiodine ((131)I). METHODS: Complete history, physical examination, complete blood count, serum biochemistries, urinalysis, blood pressure measurement, serum T4 concentration, plasma concentrations of NT‐proBNP and cTNI, and echocardiogram were obtained prospectively from each cat. RESULTS: Hyperthyroid cats and cats with HCM had plasma NT‐proBNP and cTNI concentrations that were significantly higher than those of healthy cats, but there was no significant difference between hyperthyroid cats and cats with HCM with respect to the concentration of either biomarker. In hyperthyroid cats that were re‐evaluated 3 months after (131)I treatment, plasma NT‐proBNP and cTNI concentrations as well as ventricular wall thickness had decreased significantly. CONCLUSIONS AND CLINICAL IMPORTANCE: Although there may be a role for NT‐proBNP in monitoring the cardiac response to treatment of hyperthyroidism, neither NT‐proBNP nor cTNI distinguish hypertrophy associated with hyperthyroidism from primary HCM. Therefore, the thyroid status of older cats should be ascertained before interpreting NT‐proBNP and cTNI concentrations.